Ricardo, the new view - Hollander, Samuel (Hollander, Samuel. Essays., 1995)
Samuel Hollander's interpretation of Ricardo has attracted apoplectic responses from both Right and Left. This volume collects together the material needed to evaluate these responses. His basic position - that Ricardo stands in a continuous analytical line leading from Adam Smith to Alfred Marshall - is seen to antagonise both those who argue for a 'marginal revolution' and a sharp divide between classical and neo-classical economics, and those who want to champion Ricardo as a forerunner of Sraffa.